The Role of Technology in Arabic Language Learning: Innovation and Challenges in the Digital Age - Mubarok Fatahillah; Husnul Hafidhoh (Jurnal Indonesia Sosial Teknologi, 2025)
This research aims to measure the effect of technology use in Arabic language learning on improving students' language skills at STAI Kuningan. Using a quantitative approach with a simple linear regression analysis method, this study involved 100 respondents consisting of students and teachers. Data were obtained through questionnaires distributed to respondents and analyzed to identify the relationship between technology use and Arabic language skills. The results of the study showed a significant positive relationship between the two variables. Every additional hour of technology use per week increased Arabic language skill scores by 3.679 points. The linear regression analysis showed an R Square value of 0.988, indicating that 98.8% of the variation in Arabic language skills can be explained by technology use. The validity and reliability tests of the research instrument also showed good results, with a Cronbach's Alpha value of more than 0.7. This study recommends that STAI Kuningan strengthen the use of technology in Arabic language learning to improve students' skills more effectively and efficiently.